Usability Analysis of Digital-Based Agricultural Product Marketing Platform at Farmers Level in Region V, Bogor Regency - Budiastuti, Evrina; Ritchi, Hamzah; Deliana, Yosini (Universitas Negeri Semarang, 2023)
Purpose: This study examines the usability of a digital platform called Kiosagri.com. This study needs to carry out as one of the solutions to overcome the limited accessibility of agricultural product promotion through the use of a digital platform that is expected to have usability. Therefore, this study aims to analyze the usability of digital-based agricultural product marketing platforms at the farmer level in Region V of Bogor Regency.Methods: This research employed a mixed method with an explanatory sequential design. The intended audience for the census of respondents was farmers who had utilized the Kiosagri.com platform. Data analysis was done on 32 respondents during the quantitative phase using descriptive statistics. Ten respondents were chosen purposefully for descriptive qualitative analysis during the qualitative phase.Results: According to the results, the Kiosagri platform is very user-friendly. It is achieved as a result of several beneficial aspects connected to the benefits perceived by users, such as ease of use, suitability of design, and features offered by Kiosagri.Novelty: In this study, a different way to measure the usability of digital platforms for agricultural products marketing is applied, namely by using the explanatory sequential design by conducting usability testing using descriptive statistics through the use of questionnaires and explaining the results further using descriptive qualitative through in-depth interviews which both methods are suitable for testing user experience and usability in the agricultural sector. The results of this study will be useful for the government in implementing digital marketing of agricultural products.